2022
DOI: 10.33545/26164485.2022.v6.i4g.698
|View full text |Cite
|
Sign up to set email alerts
|

Individualize homoeopathic treatment of sebaceous cyst: A case report

Abstract: Sebaceous cysts are typical, non-cancerous cysts of the skin. These cysts are unusual bodily growths that may contain liquid or semiliquid substances, even though they can occur anywhere on the body except the palms and soles. A patient suffering from painful cystic swelling for 4-5 years is presented. After case analysis and evaluation, totality was constructed and after repertorisation, the most appropriate one Sulphur 0/1 was prescribed. Alongside medication, the regular dressing was done with Calendula Q a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Published case reports, 4 5 observational study 6 and randomised controlled trial (RCT) 7 have shown positive results of homoeopathy in PCOS. However, these studies have not reported positive pregnancy outcome.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Published case reports, 4 5 observational study 6 and randomised controlled trial (RCT) 7 have shown positive results of homoeopathy in PCOS. However, these studies have not reported positive pregnancy outcome.…”
Section: Previous Studiesmentioning
confidence: 99%
“…They are more prevalent in males than female, with a ratio of 2:1. Approximately 1% of these cysts have the potential to transform into squamous cell carcinoma (SCC) or basal cell carcinoma (BCC) [1,2] . Sebaceous cysts may be singular or multiple, spherical, and smooth.…”
Section: Introductionmentioning
confidence: 99%
“…In larger cysts, an indentation may be seen at the punctum. Usually, these cysts are asymptomatic until they rupture, causing an inflammatory reaction as keratin spills into the surrounding tissue [2] . The differential diagnosis for a sebaceous cyst depends on its location and may include pilar cyst, lipoma, abscess, neuroma, benign growths, skin cancer, metastatic cutaneous lesions, ganglion cyst, neurofibroma, dermoid cyst, brachial cleft cyst, pilonidal cyst, and calcinosis cutis [2] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations